Issues in vaccine hesitancy in Malaysia: A countering approach - Wan Rohani, Wan Taib; Tengku Muhammad Ariff, Raja Hussin; Aryati, Ahmad; Noor Aini, Mohd Yusoff (2017)
Immunization has been introduced for decades to eradicate fatal infectious diseases by inoculating attenuated, killed or toxoid of microorganisms such as bacteria and virus. The triggering action to the immune system would not harm the host; despite can boost the immune responses to any infection. However, several cases of the eradicated infectious disease have re-emerged due to the existence of vaccine hesitancy group. Vaccine hesitancy has been observed emerging worldwide due to rejection in receiving vaccine. The main obstacle in vaccination program was identified according to the misconception that they received from internet or any mass media without boundaries. Various actions from the government have met the needs to enforce and educate the public especially the hesitant group towards better disease prevention with vaccination. The strategy would cover any interaction activities or programs with the public in transferring the information about the vaccination and its benefit to the health of herd community.